Elderly people and the University of Maturity (UMA): Aspects for non-adherence - Sales, Márcia Ferreira; Pontes, Fabricia Gonçalves Amaral; Pontes, Hugho Allex Neves; Souza, Josy Barros Noleto de; Lopes, Sara Janai Corado (Seven Editora, 2024)
Because the Brazilian elderly population has increased exponentially, in view of the programs that have been developed to serve this public, this article addresses the investigation on the aspects of the non-adherence of elderly people to the University of Maturity (UMA) program in a city in the northern region of Tocantins. UMA aims to expand formal knowledge, promote self-care and provide socialization, aiming at active aging. Despite the large number of elderly people in this city, few participate in the program. The main objective of this article is to investigate the factors that prevent these people from adhering to UM. The research was motivated by concern about the low participation of the elderly in the groups and by the knowledge of the positive impact that participation in these activities has on quality of life. The methodological approach adopted was qualitative, based on bibliographic, documental and exploratory research. It has been observed that in states with higher levels of education, people are more aware of the value of the UMA program and adhere more easily. On the other hand, in states with higher illiteracy rates, many older people do not understand that attending classes can be helpful for them. In short, the social dynamism and challenges faced by the elderly are still present, despite technological advances and globalization. It is necessary to take a broader look at the construction of new knowledge and conceptual transformations about the elderly, in addition to recognizing the fundamental role of education in social reintegration. DOI:https://doi.org/10.56238/sevened2023.006-131